Ambient temperature, body condition and sibling rivalry explain feather corticosterone levels in developing black kites. (5th October 2015) - López‐Jiménez, Lidia; Blas, Julio; Tanferna, Alessandro; Cabezas, Sonia; Marchant, Tracy; Hiraldo, Fernando; Sergio, Fabrizio
Summary: In birds, the steroid hormone corticosterone (CORT) is considered a major mediator in a number of physiological mechanisms and behaviours critical for the regulation of an organism's energy balance. However, the question of whether the way in which circulating plasma CORT is incorporated into feathers actually reflects this regulation, and consequently whether feather CORT (CORT‐F) measures allow to make inferences on past levels of energetic demands (also known as the allostatic load), remains unclear. While previous studies have yielded promising results, the technique still wants further study and validation in a wider range of bird species, across life‐history stages and under different ecological situations. Here, we tested whether CORT‐F levels in a sample of 427 nestling black kites ( Milvus migrans ) reflected interindividual variation in a number of environmental, social and physiological variables known to elevate allostatic load during development. We found that nestlings exposed to low ambient temperatures exhibited high CORT‐F, suggesting that feathers registered the expected rise in circulating CORT levels inducing thermogenesis in response to cold stress. CORT‐F was also negatively related to body condition, supporting the notion that allostasis becomes less affordable as energy stores become depleted. Finally, CORT‐F also reflected brood hierarchy rank, with subordinate chicks exhibiting the highest levels, followed by first‐hatched (dominant) chicks and lastly singleton nestlings. Moreover, CORT‐F levels in nestlings from multiple‐chick broods (but not in singletons) declined with age, mirroring the dynamics of establishment and stabilization of sibling hierarchies in black kites. Altogether, our results underscore the potential of using CORT‐F to infer allostatic load in wild avian populations and their potential power as indicator tools in conservation biology. Abstract : Lay Summary